Assessing visitors' preferences and willingness to pay for the Malayan Tiger conservation in a Malaysian National Park: A choice experiment method - Mzek, Tareq; Samdin, Zaiton; W. Mohamad, Wan Norhidayah (Elsevier, 2021)
The population of the unique and critically endangered species Malayan tiger (Panthera tigris jacksoni) continues to decline to less than 200 in the wild, demanding immediate attention to apply conservation plans. Thus, this study determined visitors' preferences and estimated their willingness to pay for Malayan tiger conservation attributes in Taman Negara Park in Pahang, Malaysia. Choice experiment method was used to estimate multinomial and mixed logit models. The selected attributes were related to number of tigers, tiger prey and rangers, frequency of awareness programmes, buffer zones, and conservation fee. The estimations were done with basic and interaction models of visitors' socio-demographic characteristics. Results revealed that increasing the number of tigers was the most preferred attribute with the willingness to pay varying from MYR15.42 to MYR18.07 (US$3.7 to US$4.4) between the models. The results also revealed that education and gender significantly impacted visitors' preferences. Visitors with high education level are willing to pay to increase tigers' prey. In addition, males are willing to pay to increase the awareness programme frequency, whereas females are willing to pay to increase the number of prey and rangers. These findings would support policymakers in applying an efficient conservation budget allocation to develop conservation management plans.